PENGARUH GOOD GOVERNANCE, BUDAYA ORGANISASI, GAYA KEPEMIMPINAN, KOMITMEN ORGANISASI, DAN PENGENDALIAN INTERN TERHADAP KINERJA PEMERINTAH DAERAH (Studi Empiris- Pada SKPD Kabupaten Pelalawan) - Muhammad Andri Prayoga; Desmiyawati '; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to test the Effect of Good Governance, Organization Culture, Leadership Style, Organizational Commitment and Intern Control on Local Government Performance (Study In SKPD of Pelalawan). The location of this research is all SKPD of Pelalawan Regency. In this study, the population used is SKPD of Pelalawan Regency. Respondents in this study is the structural officials involved in drafting the budget. In total there are 31 SKPD. Every SKPD will be given three questionnaires, so the number of questionnaires distributed is 93 pieces. The data used are primary data. Data Collection Techniques of field research and literature. The analytical method used in this research is multiple regression analysis.Based on the analysis, the conclusions of this research are: 1) There is a significant effect of Good Governance on Local Government Performance. 2) There is a significant effect of Organization Culture on Local Government Performance. 3) There is a significant effect of Leadership Style on Local Government Performance. 4) There is a significant effect of Organizational Commitment on Local Government Performance. 5) There is a significant effect of Intern Control on Local Government Performance. Based on the research results it was concluded that the determination coefficient is 61.6%. It means that 61.6% of Local Government Performance variations can be explained by the variable Good Governance, Organization Culture, Leadership Style, Organizational Commitment and Intern Control. While 38.4% is explained by other variables outside the model.Keywords: Good Governance, Organization Culture, Leadership Style, Organizational Commitment, and Intern Control